Strategi Peningkatan Penerimaan Mahasiswa Baru di Perguruan Tinggi Swasta (Studi Kasus: Universitas Muhammadiyah Gresik) - Sholihah, Vina Mar'atus; Kurniawan, Aries; Ismanto, Hadi; Rahmi, Vembri Aulia; Respati, Putra Panji (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
The impact of the Covid-19 pandemic, particularly on job losses among prospective students' parents, was the primary factor behind the decline in admissions in 2020. Additionally, the introduction of new study programs in 2019 and competition among universities in nearby areas also contributed to this fluctuation. The purpose of this analysis is to identify the causes of enrollment fluctuations and develop strategies to increase new student admissions at Universitas Muhammadiyah Gresik. This will lead to effective strategies to address these challenges and create programs that attract new students to register at Universitas Muhammadiyah Gresik. This research employs a qualitative method, with information obtained through interviews with relevant subjects, including the Head of Admissions & Public Relations from 2019-2023, Heads of Department, Admissions Officers, several students from 2023, and some prospective students for 2024. Analysis shows that online promotional strategies are highly effective, but personal connections and accreditation strengthening are also crucial. Altogether, these strategies successfully align the university with the dynamics of the higher education market. Recommendations are made to continue developing adaptive strategies to enhance the university’s appeal in the increasingly competitive higher education landscape.